If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5(-1x + -16) = 68 Reorder the terms: -3x + -5(-16 + -1x) = 68 -3x + (-16 * -5 + -1x * -5) = 68 -3x + (80 + 5x) = 68 Reorder the terms: 80 + -3x + 5x = 68 Combine like terms: -3x + 5x = 2x 80 + 2x = 68 Solving 80 + 2x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + 2x = 68 + -80 Combine like terms: 80 + -80 = 0 0 + 2x = 68 + -80 2x = 68 + -80 Combine like terms: 68 + -80 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| -3(x+8)+4(x+9)=2x | | 14+6M-2-3M=5M+8 | | 5x^2-10x+6y^2+36y+60=0 | | 5w^2=35w | | 12m-2m+3+4m=31 | | 12-2m+3+4m=31 | | 9v^2+9v-40=0 | | 6+8m+8=12m+2+4 | | 6+8m=12m+2+4 | | 8(m+4)(2m-1)= | | 9x+4x=0.9-1.4 | | 3M+15=5m+9 | | 5M+40=100 | | 100=5M+40 | | 151=7x-6(-3x+4) | | 2x-3.4=x-3.6 | | 2xy=x^6+y^6 | | 57.6=240(0.03)t | | 3x-13+4x-24=180 | | 1half(6x-8)=41 | | 3x-13=4x-24 | | 4x+2[4-2(x+2)]=2x-1 | | 4(m-4)=12 | | 18.8=2(3.14)r | | 22=2l+2(7) | | Y=x^5-1x^3-6x | | 9y=-45x+45 | | -y^2+9y-9=0 | | 2x+10=20x-20 | | 5m*5m+27m+34=0 | | x=2y+2 | | 4y^2+16y+18=0 |